The key role of intercultural competencies for effective integration: from theory to practice - Stella Pinna Pintor; Viviana Premazzi (Quality Education for All)
Purpose – The purpose of this study is to explore how intercultural competencies impact the employment of young people, and to showcase virtuous examples of practices by the University of Turin and the company Global Mindset Development. Design/methodology/approach – Drawing upon a comprehensive review of relevant literature, this paper highlights the theoretical foundations of intercultural competencies and their relevance to labor market integration. It examines their multidimensional nature, encompassing knowledge, skills, attitudes and awareness necessary for individuals to effectively navigate and engage with diverse cultural contexts. The paper then presents several good and promising practices realized by the University of Turin and the training and consultancy company Global Mindset Development. Furthermore, it addresses potential challenges associated with developing and implementing intercultural competencies in practice. Findings – The study enriches the body of literature on the importance of intercultural competencies for young workers acquired through experiences such as international mobility for labor market integration. Originality/value – The study presents some innovative approaches to training through experiential and mobility training programs. These new examples of practices can inspire further research and implementation.